Association Ramondo – Ostryetum carpinifoliae ass. nova. - Berisha, Naim; Millaku, Fadil; Gashi, Bekim; Matevski, Vlado (Hacquetia, 2019)
The genus Ramonda in Europe is represented with three species: Ramonda nathaliae Pančić & Petrovič, Ramonda serbica Pančić and Ramonda myconi (L.) Rchb. The first two are endemic Balkan species that are distributed also in Kosovo. These species grow in limestone as well as serpentine substrates, forming chasmophytic vegetation. The species Ramonda nathaliae is found in the Northern and Central parts of Macedonia, Northern Greece, South-Eastern Serbia and in two localities within Kosovo, Sharri Mountains (Luboten and Gotovushë). R. nathaliae in serpentines of Macedonia forms the following plant associations: Asplenio-Ramondetum nathaliae and Scorzonero–Ramondetum nathaliae, while in limestone substrates forms the ass. Achilleo–Ramondetum nathaliae. Ostrya carpinifolia Scop. within the order Quercetalia pubescenti–petraeae, alliance Fraxino orni–Ostryion forms the ass. Querco pubescentis – Ostryetum carpinifoliae. Within the order Fagetalia sylvaticae, alliance Aremonio–Fagion it forms the ass. Ostryo–Fagetum, while within the alliance Fraxino orni–Ostryion it forms the ass. Querco–Ostryetum carpinifoliae and ass. Corylo colurnae–Ostryetum carpinifoliae. The phytocoenological research studies were made using the principles and methods of the Zürich–Montpellier School. This paper presents plant communities of Ramonda nathaliae and Ostrya carpinifolia Scop. on limestone habitat, where the new proposed plant association named Ramondo–Ostryetum carpinifoliae ass. nova. is described. This plant community belongs to the class Quercetea pubescentis, order Quercetalia pubescenti-petraeae and alliance Fraxino orni-Ostryion. This plant community was found and described on the limestone substrate in Luboteni Mt. (960 - 982 m. a.s.l.), Republic of Kosovo, close to the border with Republic of Macedonia.